Evaluation of brain microstructure changes in surviving fetus of monochorionic twin pregnancies with single intrauterine fetal death using diffusion weighted imaging: a MRI-based cohort study - Aonan Wang; Ran Huo; Yuan Wei; Xiaoyue Guo; Zheng Wang; Qiang Zhao; Ying Liu; Huishu Yuan (BMC Medical Imaging)
Abstract Background Single intrauterine fetal death (sIUFD) will lead to an increased risk of adverse events such as fetal brain abnormalities in the survivor. However, how to detect these anomalies in the early stages remains to be explored. Objective To compare apparent diffusion coefficient (ADC) values of fetal brain in cases of single intrauterine fetal death (sIUFD) with twins control and singleton control using diffusion weighted imaging (DWI), and to perform follow-up study to reveal the underlying cerebral microstructure changes. Materials and methods In this prospective MRI-based cohort study, we compared 43 surviving fetuses of sIUFD (18 following selective fetal reduction, 2 following laser ablation treatment for twin-to-twin transfusion syndrome, and 23 spontaneous) with 2 control cohorts ( 43 healthy twin fetuses, 43 singletons). All fetuses underwent fetal brain MRI. DWI was performed and ADC map was reconstructed. ADC values of certain regions were compared among the three groups. Results ADC values were lower in bilateral white matter of frontal, parietal, temporal lobes and cerebellum in surviving fetuses compared with twins control and singleton control, respectively. ADC values of bilateral basal ganglia, thalamus and cerebellum in surviving fetuses, that of bilateral frontal lobes, cerebellum in twins control and that of right temporal lobe, left basal ganglia, and bilateral cerebellum in singleton control, were negatively correlated with gestational age. ADC values of left cerebellum in surviving fetuses were positively correlated with interval time. Conclusions DWI is a very useful sequence for detecting underlying changes. ADC value might be a effective indicator of subtle anomalies in surviving fetuses.